Sagittal Plane Mobility in Adolsents with Femoroacetabular Impingment. Issue 5 (31st May 2022) - Johnson, Benjamin L.; Cooper, Savannah; Wilson, Philip L.; Morris, William; Ellis, Henry B.
Background: Femoroacetabular impingement (FAI) is a dynamic degradative condition of the hip joint characterized by classic physical exam findings in combination with abnormal radiographs and/or MRI. Although this abnormal morphologic relationship contributes to FAI, the role of physical therapy to mitigate symptoms by improving strength and mobility of the hip remains the first line treatment. Despite this common treatment algorithm, limited knowledge exists on the effects of sagittal balance, lumbopelvic mobility, and its role in the development of treatment for symptomatic FAI. Hypothesis/Purpose: To review lumbopelvic mobility from standing to sitting position in adolescent athletes who present with clinical signs of FAI. Methods: Pelvic radiographic measurements in the sagittal plane were performed on a retrospective series of consecutive patients who presented with clinical diagnosis of FAI at a pediatric sports medicine institution from April 2019-March 2021. Standardized EOS dynamic lateral pelvic images were performed in standing and sitting positions to evaluate the differences in sacral slope, pelvic tilt, and pelvic incidence. Data from bi-positional radiographs were combined with standard measurements for FAI obtained on AP pelvis (lateral center edge angle, acetabular inclination) and 45 degree Dunn views (alpha angle), and patient reported outcomes (PROs) (mHHS, HOOS, UCLA). Differences in sacral slope from pre-treatment radiographs were used to determine comparison groups: those with a change vs. those with limited change between a sitting and standing position. Results: 76 adolescent patients (mean age 15.7 years [12-24]; 71.5% females) with sitting/standing lateral pelvis radiographs and a clinical diagnosis of FAI were identified. Between sitting and standing positions, there was no change in pelvic incidence, while significant differences were noted in sacral slopes and pelvic tilt (Table 1). Variability in sacral slope differences between sitting and standing were identified with 10 (13.9%) patients having minimal (<10 o ) change, while 8 (11.1%) demonstrated changes > 40 o (Figure 1). Adolescent patients with FAI who demonstrated more mobility from sitting to standing position had a higher sacral slope in the standing position. No correlations were noted between pelvic incidence or sacral slope and radiographic measures associated with FAI, PROs or differences in those with variable changes in sacral slope from sitting to standing position. Conclusion: Lateral pelvic imaging may be an important tool for understanding dynamic hip impingement. In adolescent patients signs and symptoms with clinical FAI, significant variability exists in lumbopelvic mechanics, regardless of the severity of radiographic values. Table 1. Radiographic measurements performed on a sitting and standing lateral pelvic radiographs using EOS. Values listed are mean (standard deviation; range). Figure 1. Sitting and Standing lateral pelvic images from 2 patients. Top row: Standing lateral pelvis (A) and sitting lateral pelvis (B) with a significant change in sacral angle and pelvic tilt with no changes in pelvic incidence. Not the change in lumbar lordosis in this patient. Bottom row: Standing lateral pelvic (A) and sitting lateral pelvic (B) without significant change in lumbosacral position.